Meiotic gene expression initiates during larval development in the sea urchin - Yajima, Mamiko (2012)
BACKGROUND: Meiosis is a unique mechanism in gamete production and a fundamental process shared by all sexually reproducing eukaryotes. Meiosis requires several specialized and highly conserved genes whose expression can also identify the germ cells undergoing gametogenic differentiation. Sea urchins are echinoderms which form a phylogenetic sister group of chordates. Sea urchin embryos undergo a feeding, planktonic larval phase in which they construct an adult rudiment prior to metamorphosis. Although a series of conserved meiosis genes (e.g. dmc1, msh5, rad21, rad51, and sycp1) are expressed in sea urchin oocytes, we sought to determine when in development meiosis would first be initiated. RESULT: We surveyed the expression of several meiotic genes and their corresponding proteins in the sea urchin Strongylocentrotus purpuratus. Surprisingly, meiotic genes are highly expressed not only in ovaries but beginning in larvae. Both RNA and protein localizations strongly suggest that meiotic gene expression initiates in tissues that will eventually give rise to the adult rudiment of the late larva. CONCLUSIONS: These results demonstrate that broad expression of the molecules associated with meiotic differentiation initiates prior to metamorphosis and may have additional functions in these cells, or mechanisms repressing their function until later in development, when gametogenesis begins.